Debate on Patriarchal Interpretation of Misogynist Hadith - Chaniago, Salsabila Najma (Yayasan Albahriah Jamiah Indonesia, 2025)
Criticism of hadith as a source of law in Islam is still debated today. For some reason, the hadith has been overlooked as an infallible source, and its authenticity is often the subject of debate among past and present scholars. One of the important debates in hadith studies is the existence of misogynist traditions which are claimed to exist in the ṣaḥīḥ hadith collection. This article aims to find out how this hadith has been criticized because it is influenced by patriarchal interpretation and anti-women prejudice as claimed by feminists. This is caused by male dominance in various key aspects of Islamic texts, including the processes of transmission, preservation, publication and interpretation. Unfortunately, the interpretation of hadith, especially those relating to women, contains gender bias and discrimination against women. Feminists argue that these hadiths are interpreted in the interests of men and patriarchal culture. Apart from that, this research also tries to examine several reasons for rejecting patriarchal interpretations initiated by feminists, with the aim of rejecting anti-women discourse and emphasizing women-friendly interpretations of Islamic texts. These findings indicate that patriarchal interpretation may be the reason for the persecution of women, but the hadith contains equal divine wisdom for both sexes. It is a shared responsibility to provide a better understanding of hadith textually and contextually.